2015
DOI: 10.4103/1947-2714.152077
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of copper deficiency on activity of superoxide dismutase in diabetic nephropathy

Abstract: Background:Copper (Cu) is essential both for its role in antioxidant enzymes, like Cu/zinc (Zn) superoxide dismutase (SOD) and ceruloplasmin, as well as its role in lysyl oxidase, essential for the strength and integrity of the heart and blood vessels. With such a central role in cardiovascular health, Cu has been generally overlooked in the debate over improving our cardiovascular health. Cu deficiency has produced many of the same abnormalities present in cardiovascular disease. It seems almost certain that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…The supplements of antioxidant mixtures consisted of combinations of 2 or more of the following: vitamin A, retinol, β-carotene, vitamin C, vitamin E, selenium, zinc, and copper as composite entities. These antioxidants were selected because they were included in the 2012 Cochrane Review ( 21 ), to which we added retinol as part of vitamin A as well as zinc and copper as metals associated with the synthesis or activity of the endogenous antioxidant system ( 22 , 23 ). The antioxidants used in specific studies included in this analysis are shown in Supplementary Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The supplements of antioxidant mixtures consisted of combinations of 2 or more of the following: vitamin A, retinol, β-carotene, vitamin C, vitamin E, selenium, zinc, and copper as composite entities. These antioxidants were selected because they were included in the 2012 Cochrane Review ( 21 ), to which we added retinol as part of vitamin A as well as zinc and copper as metals associated with the synthesis or activity of the endogenous antioxidant system ( 22 , 23 ). The antioxidants used in specific studies included in this analysis are shown in Supplementary Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Copper deficiency, by reducing levels of SOD, can lead to reductions in NO, which in turn leads to reduced endothelial function, lower vasodilation and increased oxidative stress, all of these being hallmarks of atherosclerosis. 28 Copper deficiency also reduces liver and plasma selenoglutathione peroxidase. 29 …”
Section: Introductionmentioning
confidence: 99%
“…Humans with diabetic nephropathy show significantly lower plasma levels of SOD, as well as an increased urinary copper excretion. 28 Both of these factors may play a role in the increased incidence of IHD seen in diabetics. Thus, in individuals with diabetes and microalbuminuria, lower SOD and lower copper levels could promote IHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Серед основних цільових напрямків досліджень ОС у діалізних пацієнтів є визначення особливостей змін О/А показників залежно від процедур діалізу та типу діалізних мембран; дослідження впливу модальності ДНЗТ на О/А показники; дослідження змін О/А показників за умов розвитку ССУ у таких пацієнтів [33,34,37], за наявності у них гіпертензії [24], порушень нутриційного статусу [19,50], розвитку хронічного запалення [19,47,52] та за наявності анемії, яка теж є прооксидантим станом [12].…”
unclassified